ANALISIS STRATEGI DIGITAL MARKETING KOPI SEJUTA JIWA - Nazarudin Ahsani; Christian Wiradendi Wolor; Eka Dewi Utari (CV. Denasya Smart Publisher, 2025)
This study aims to explore the influence of Kopi Sejuta Jiwa's TikTok content on students' purchasing decisions and to identify non-digital factors that also influence these decisions. This study uses a qualitative approach with a case study design, with primary data obtained through interviews with four students from different batches who have purchased Kopi Sejuta Jiwa products and are active TikTok users. Secondary data was obtained through observation of three TikTok content with the highest interaction from the official Kopi Sejuta Jiwa account. The results of the study indicate that students' purchasing decisions are more influenced by price, taste, location, and personal experience, while TikTok content is considered to have the potential to influence if it is packaged attractively and does not feel overly promotional. Content observation revealed that despite varied content approaches, engagement levels remain relatively low. This study concludes that digital marketing strategies need to be optimized through relevant, inspirational, and interactive content, while still balancing quality products and direct services.